The Creed of Ahl al-Sunnah wa al-Jamaah and The Coming Challenges to Muslims in Malaysia - Alwi, Engku Ahmad Zaki bin Engku (Proceedings of International Conference on Islamic Civilization and Humanities, 2023)
The creed of ahl al-sunnah wa al-jamaah (the people of the sunnah and the community) is the largest denomination of Islam, followed by the majority of Muslims in the world. In the case of Malaysia, Islam has been acknowledged as the religion of the Federation, while ahl al-sunnah wa al-jamaah is well accepted as a Muslim creed and serves as the main source of reference, especially in matters arising from Islamic doctrine. However, it is undeniable that there are other creeds that do not conform to this creed, such as Shia and Qadiyani, as well as modern Western ideologies such as humanism, pluralism, liberalism, rationalism, and so on. These distorted theological sects and ideologies practice some deeds that are contrary to Islamic law, such as mut’ah or temporary marriage, intense devotion to a particular individual, defining the legal ruling using logical reasoning, and so on. These phenomena have led to misunderstandings, especially among the young generation, thus leading to negative cultural practices that would impede the survival of the Muslim civilization in Malaysia. Therefore, this qualitative study is developed based on library research data. As a result, this article aims to elucidate the framework of ahl al-sunnah wa al-jamaah creed that should be preserved to keep up with the coming challenges to Muslims. Subsequently, it proposes several efforts and solutions that need to be considered to preserve the survival and status of this creed in Malaysia.